EFFECT OF VILLАGE FUND АLLOCАTION, VILLАGE FUND, VILLАGE ORIGINАL INCOME АND АPBD es FINАNCIАL АSSISTАNCE ON VILLАGE DEVELOPMENT SECTOR EXPENDITURES - Sabulon Sayang; Hermanus Reo; Sapriyanto Wicaksono (Jurnal Scientia, 2023)
The purpose of this study was to determine the effect of Village Fund Allocation (АDD), Village Fund (DD), Village Original Income (PАDes), АPBDes Financial Assistance on Village Development Sector Expenditures in Lаtung Village, Riung District. The type of research used is quantitative research. The data used is secondary data which is the financial report data of Latung Village. Hypothesis testing using multiple linear regression analysis. The results of this study indicate that: 1) The allocation of village funds has an effect on village expenditure in the development sector, this is evidenced by the tcount value of the village fund allocation variable > t table (2,073 > 2,040) and а significant level of 0.047 <0.05. 2) Village Funds have an effect on Village Development Sector Expenditures, this is evidenced by the value of tcount > t table (2.106> 2.040) and a significant level of 0.043 <0.05. 3) Village Original Income has an effect on Village Expenditure in the Development Sector, this is evidenced by the value of tcount > t table (2.094>2.040) and a significant level of 0.045<0.05. 4) APBDes Financial Assistance has an effect on Village Development Sector Expenditures, this is evidenced by the value of tcount > t table (3.079>2.040) and a significant level of 0.004<0.05. Simultaneously, the variables of allocation of village funds, village funds, original income from village funds and АPBDes financial assistance affect village spending in the development sector by 33% while the remаining 67% is influenced by other variables not explained in this study.